2013
DOI: 10.1080/09540121.2013.764395
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the community response to HIV and AIDS: Learning from a portfolio approach

Abstract: While communities have played a large role in the HIV/AIDS response, their contributions and innovative approaches to HIV prevention, treatment, care and support have not always been the focus of systematic and rigorous evaluations. To address this gap, the World Bank led an evaluation of the impact of the community response to HIV, including country studies in Burkina Faso, India, Kenya, Lesotho, Nigeria, Senegal, South Africa and Zimbabwe over a three-year period. Due to the complexity and varied nature of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 7 publications
(8 reference statements)
0
11
0
Order By: Relevance
“…An interesting finding regarding all the initiatives towards the establishment of Ruvheneko is that the severity of HIV and AIDS in Chirumhanzu created some kind of fear of the unknown to the extent that members felt obliged to be part of the programme. This resonates with Rodriguez-Garcia’s (2013) model of social change that looks at how social challenges foster social cohesion and collectively problem solving approaches. This also reveals grassroots response to the impact of HIV and AIDS since the community improvised some self-help mechanisms in order to respond to such social challenges like AIDS (Rodriguez-Garcia, 2013).…”
Section: Discussion Of Findingsmentioning
confidence: 54%
See 1 more Smart Citation
“…An interesting finding regarding all the initiatives towards the establishment of Ruvheneko is that the severity of HIV and AIDS in Chirumhanzu created some kind of fear of the unknown to the extent that members felt obliged to be part of the programme. This resonates with Rodriguez-Garcia’s (2013) model of social change that looks at how social challenges foster social cohesion and collectively problem solving approaches. This also reveals grassroots response to the impact of HIV and AIDS since the community improvised some self-help mechanisms in order to respond to such social challenges like AIDS (Rodriguez-Garcia, 2013).…”
Section: Discussion Of Findingsmentioning
confidence: 54%
“…This resonates with Rodriguez-Garcia’s (2013) model of social change that looks at how social challenges foster social cohesion and collectively problem solving approaches. This also reveals grassroots response to the impact of HIV and AIDS since the community improvised some self-help mechanisms in order to respond to such social challenges like AIDS (Rodriguez-Garcia, 2013). As noted by Schwobel (2006), it is precisely when human dignity is compromised that it becomes imperative for the church to engage in critical and affirmative public theology.…”
Section: Discussion Of Findingsmentioning
confidence: 54%
“…A growing body of literature demonstrates that communitybased services have measurable impact, serve populations that are not accessing public health services [7] and can reach people at scale [8,9]. A 2012 World Bank study identified community-based efforts as a ''cornerstone'' of the response to AIDS [10].…”
Section: Discussionmentioning
confidence: 99%
“…From the annals of lived experience, we have always known the solutions that are needed for people who use drugs. The essential role of communities in the HIV movement reshaped the global health agenda in critical ways, including drawing the world's attention to the social-structural determinants of health, biopower and biopolitics and embedding the principle of meaningful community involvement within the rigid and depersonalised corridors of public health (Foucault, 1976;Rodriguez-García et al, 2013). Today, these past lessons are being brought into sharper focus.…”
Section: Communities: Solidarity Dignity and Cooperationmentioning
confidence: 99%